Proceedings of the International Conference on Administrative Science (ICAS 2017) 2017
DOI: 10.2991/icas-17.2017.29
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Leadership in the Implementation of Administrative Reform at the Indonesian National Institute of Public Administration

Abstract: Abstract-Most administrative reforms in public organizations have not produced substantial changes, neither in structure, nor process nor attitude. Leaders in such organizations tend to prefer to implement reform as a formality or simply to comply with rules and legislations, given the great risks they will face. This condition has encouraged a review of the role of leadership that must be undertaken so that substantive changes in public organizations can occur. A case study was conducted on an administrative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Parra (2016) similarly demonstrates that at the societal level, there is a link between leadership and project implementation. Kamaruddin and Prasojo (2017) also support this relationship at the organizational level. Thus, in view of the context considered for this study, it is suggested that an important outcome of leadership when it is in operation in a context focusing on societal development is that of societal impact arising from successful project implementation.…”
Section: Community Development Impactsupporting
confidence: 55%
“…Parra (2016) similarly demonstrates that at the societal level, there is a link between leadership and project implementation. Kamaruddin and Prasojo (2017) also support this relationship at the organizational level. Thus, in view of the context considered for this study, it is suggested that an important outcome of leadership when it is in operation in a context focusing on societal development is that of societal impact arising from successful project implementation.…”
Section: Community Development Impactsupporting
confidence: 55%
“…Effective supervisory management should consistently strive to enhance the quality of instruction and boost instructional achievement. They should assist teachers in setting and fostering high expectations while establishing direct connections with teachers and the classroom (Portin et al, 2013). Zepeda (2017) highlights a notable connection between instructional, supervisory management and professional development.…”
Section: Selfmentioning
confidence: 99%